Albers - Appel - Arp - Bissier - Cesar - Chadwick - Dubuffet - Ernst - Fautrier - Francis - Giacometti - Hartung - Herbin - Hepworth - Hoflehner - Marini - Mathieu - Matta - Moore - Nevelson - Picasso - Polakoff - richier - Riopelle - Schwitters - Soulages - De Stael - Vasarely - Viera da Silva. (Zürich : Gimpel und Hanover Galerie, 1962)
Albers, Josef ; Appel, Karel ; Arp, Hans (Jean) ; Bissier, Julius ; César ; Chadwick, Lynn ; Dubuffet, Jean ; Ernst, Max ; Fautrier, Jean ; Francis, Sam ; Giacometti, Alberto ; Hartung, Hans ; Hepworth, Barbara ; Herbin, Auguste ; Hoflehner, Rudolf ; Marini, Marino ; Mathieu, Georges ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Moore, Henry ; Nevelson, Louise ; Picasso, Pablo ; Poliakoff, Serge ; Richier, Germaine ; Riopelle, J.P. ; Schwitters, Kurt ; Silva, Vieira da ; Soulages, Pierre ; de Staël, Nicolas ; Vasarely, Victor
biografie
Albers - Appel - Arp - Bissier - Cesar - Chadwick - Dubuffet - Ernst - Fautrier - Francis - Giacometti - Hartung - Herbin - Hepworth - Hoflehner - Marini - Mathieu - Matta - Moore - Nevelson - Picasso - Polakoff - richier - Riopelle - Schwitters - Soulages - De Stael - Vasarely - Viera da Silva, Gimpel und Hanover Galerie, Zürich, 16. November 1962 bis 5. Januari 1963
Duits & Engels
kunstcatalogus